Efferocytosis in the Central Nervous System - Zhao, Jiayi; Zhang, Weiqi; Wu, Tingting; Wang, Hongyi; Mao, Jialiang; Liu, Jian; Zhou, Ziheng; Lin, Xianfeng; Yan, Huige; Wang, Qingqing (Frontiers in Cell and Developmental Biology, 2021)
The effective clearance of apoptotic cells is essential for maintaining central nervous system (CNS) homeostasis and restoring homeostasis after injury. In most cases of physiological apoptotic cell death, efferocytosis prevents inflammation and other pathological conditions. When apoptotic cells cannot be effectively cleared, the destruction of the integrity of the apoptotic cell membrane, leakage of intracellular contents, and secondary necrosis may occur. Efferocytosis is the mechanism by which efferocytes quickly remove apoptotic cells from tissues before they undergo secondary necrosis. Cells with efferocytosis functions, mainly microglia, play a role in the elimination of apoptotic cells from the central nervous system. Here, we will discuss the impact of efferocytosis on homeostasis, the mechanism of efferocytosis, the relationship between the failure of efferocytosis and disease of the central nervous system, the current clinical application of efferocytosis, and to provide efferocytosis as a novel potential target for exploring the causes and solutions of central nervous system diseases.